Schistosoma japonicum and S. mansoni cercariae: different effects of protein in medium, of mechanical stress, and of an intact complement system on in vitro transformation to schistosomula - Wang, Wenshi; Kirschfink, Michael; Ruppel, Andreas (Parasitology research, 2006)
The cercariae of Schistosoma japonicum were subjected in vitro to treatments known for Schistosoma mansoni to generate schistosomula-like organisms. As a technical prerequisite to pipette or to otherwise handle the sticky cercariae of S. japonicum, the addition of protein to water or medium was found to abolish the stickiness of cercariae of this species. Shearing forces exerted in vitro by syringe (22 G) passage are known since long to fully transform S. mansoni cercariae, but this treatment was found to be much less efficient with S. japonicum. Thus, even with very narrow needles (27 G), complete transformation of cercariae was not obtained with S. japonicum. Complement, provided by fresh human serum, is also well known to induce rapid transformation of S. mansoni cercariae with subsequent killing of the schistosomula. This treatment of S. japonicum cercariae induced degeneration of the tails and strongly promoted the transformation to schistosomula-like organisms, but at a much slower pace. These effects were absent from sera either heat-inactivated or depleted of factor B or of complement component C8, but were restored after adding the purified respective complement components. The schistosomula-like organisms of S. japonicum were not susceptible to lysis after 1 day of in vitro culture in the presence of 50% fresh human serum, although both cercariae and schistosomula of S. mansoni were killed under these conditions. In conclusion, the dynamics of in vitro transformation of S. japonicum cercariae differ significantly from those of S. mansoni, and complement has a major transformation-promoting activity.
Gesehen am 21.06.2021